(untitled) (Memorandum: Memory and History in Psychology, 2002)
In this report we have dealt with three ways of enriching words by visual images: Slides, books on pictorial history of psychology, and videos. We noted films produced in the 1960s by R. I. Evans. Each approach has its limitations and its merits. Taken all together, they constitute a significant addition to the printed word and to lectures, thus broadening the tool kit of both the learners and teachers of the history of psychology.